(untitled) (Bangladesh Journal of Child Health, 2012)
Objective: Tetralogy of Fallot (TOF) is the commonest cause of cyanotic congenital heart disease (CHD) worldwide. The aim of this study was to determine the demography, associated anomalies and status of peripheral pulmonary stenosis (PPS), type of operation, operative results and complications in TOF physiology patient. Materials & Methods: The records of 52 patients were reviewed. These patients were admitted from January 2007 to November 2009 in United Hospital Limited, Dhaka. Results: Male patients were 61.5% and females were 38.5%. The median age of surgery was 5 years and weight was 15 kg with severely undernourished patients were 27% and severely stunted were 11.5% respectively. Among the associated anomalies, percentage of patent ductus arteriosus (PDA), patent foramen ovale (PFO) / atrial septal defect (ASD), right aortic arch (RAA), coronary artery (CA) anomalies and peripheral pulmonary artery stenosis were 57.7%, 26.9%, 21.2%, 11.5% and 13.5% respectively. 13.5% TOF physiology patient had severely hypoplastic pulmonary annulus, 38.4% had severely hypoplastic MPA. TOF was more common in B blood group patients. About 11.5% patients underwent palliative operation (Gore-tex shunt) as the first operation. The youngest case was 7 days and the oldest 7.5 years old. Corrective operation, TC (Total correction) was done in 94%cases. The youngest patient undergoing TC was 1.5 years and the oldest one was 40 years old. Transannular patch (TAP) was used in 24 cases (46%). Post surgical overall mortality rate was 23% in three year which was 17.3% in 1st year, 3.84% in 2nd year and 1.92% 3rd year. Conclusion: In this study total correction (TC) was done in most of the cases (94%) and this should be recommended as the preferred management strategy for TOF physiology patient. The mortality rate decreases significantly as the team get experienced. DOI: http://dx.doi.org/10.3329/bjch.v34i3.10358 BJCH 2010; 34(3): 86-91